Revitalizing Potential Economic Through Digital Entrepreneurship for Female Inmatesat Bandar Lampung Prison - Arfi Darmawan; Laili Fadhila Banuwa; Ambya; Sri Andayani; Hafidz Izzudin Alfaruq; Rr. Keisha Ayu Putri Namira; Dita Akmalia Fauziah (Madani : Indonesian Journal of Civil Society, 2026)
The Digital Entrepreneurship School program targets convicts at the Class IIA Women's Correctional Institution in Bandar Lampung who have minimal digital literacy and limited product marketing skills. The program included 25 productive- age convicts (20 to 50 years old). The methodology comprised education, interactive training, technology distribution, and aid with promotional material development and internal exhibitions. Pre- and post-test evaluations revealed considerable gains in all areas, with digital marketing comprehension showing the greatest rise (+0.76). Aside from technical capabilities and enhanced self-confidence, participants displayed the capacity to create independent promotional content. This initiative demonstrates that digital entrepreneurship improves creative economic potential while minimizing social stigma for convicts. These findings underscore the value of digital empowerment models as a long-term and inclusive social reintegration.